The Importance of Dialectal Variation in Kerala Curriculum Framework - Pappachan, Princy (Middle Eastern Journal of Research in Education and Social Sciences, 2020)
Purpose: From prior research, language variation is observed to beneficially influence the field of education. Following this hypothesis, the study verifies the importance of dialectal variations in a language, specifically in Malayalam. The study strives to answer the need for linguistic equality and how this can be achieved through the curriculum. Approach/Methodology/Design: A mixed method approach was adopted using questionnaire and personal interviews. Data was collected from University students between the age group 20-30. The material of the study involved different lexical items. The data was analyzed by accounting the number of occurrences and its percentage. Pivot chart was tabulated of the percentage of dialectal variations lexical items against each participant in different category. Findings: The study revealed the lack of awareness of dialectal variations that existed in the selected lexical items. This neglect provides an evidence of the progressing decline in language lexicon that is detrimental to language growth and preservation of vocabulary. The study illustrates how this can be rectified through the curriculum by incorporating dialectal variations in the textbooks. Practical Implications: The study will contribute positively to understanding the importance of incorporating dialectal variations to preserve the existing language lexicon by accommodating the non-standard variation. This step ensuring the equality of regional elements would help in an effective and successful learning of language. Originality/value: This study takes into consideration the regional variations that exist in Malayalam language spoken in Kerala. The study provides a base for further research into mapping dialectology.